2015
DOI: 10.3153/jfhs15019
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF SHELF LIFE OF MARINADE AND BRINE INJECTED RAINBOW TROUT (Oncorhynchus mykiss, WALBAUM 1792) AT REFRIGERATOR CONDITIONS

Abstract: Abstract:The aim of this study was to determine quality changes occurring in refrigerator (3 ±1ºC) of rainbow trout (Oncorhynchus mykiss) was injected marinade brine and salt brine. The trouts were stored into 3 groups as control, marinade (4% acetic acid-8% salt) injected and brine (20% salt) injected groups. Moisture, crude protein and crude fat of fresh trout were found 78.04%, 16.83% and 4.18%, respectively. Total volatile basic nitrogen (TVB-N) and thiobarbituric acid (TBA) values were determined below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The initial TVB-N value of rainbow trout was 13.30 mg/100 g, and TVB-N value of all croquette groups increased significantly (p < .05) according to storage time (Figure 4b). TVB-N value of fresh rainbow trout is consistent with the values (14.08 mg/100 g) reported by Çağlak and Karslı (2015). In this study, dill extracts showed a delaying effect on the increase of TVB-N values, and TVB-N values of croquette groups (BDA and DDA) were found significantly lower over storage time (p < .05).…”
Section: Chemical and Physical Quality Parameterssupporting
confidence: 91%
“…The initial TVB-N value of rainbow trout was 13.30 mg/100 g, and TVB-N value of all croquette groups increased significantly (p < .05) according to storage time (Figure 4b). TVB-N value of fresh rainbow trout is consistent with the values (14.08 mg/100 g) reported by Çağlak and Karslı (2015). In this study, dill extracts showed a delaying effect on the increase of TVB-N values, and TVB-N values of croquette groups (BDA and DDA) were found significantly lower over storage time (p < .05).…”
Section: Chemical and Physical Quality Parameterssupporting
confidence: 91%